2017
DOI: 10.1186/s12938-017-0333-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling electrical stimulation of retinal ganglion cell with optimizing additive noises for reducing threshold and energy consumption

Abstract: BackgroundEpiretinal prosthesis is one device for the treatment of blindness, which target retinal ganglion cells (RGCs) by electrodes on retinal surface. The stimulating current of epiretinal prosthesis is an important factor that influences the safety threshold and visual perception. Stochastic resonance (SR) can be used to enhance the detection and transmission of subthreshold stimuli in neurons. Here, it was assumed that SR was a potential way to improve the performance of epiretinal prosthesis. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…What remains unknown is whether tRNS-induced signal enhancement, and related contrast sensitivity benefits, could be achieved at the retinal level. Modelling studies suggest noise benefits in retinal ganglion cells ( Patel and Kosko, 2005 ) induced by both visual ( Ghosh et al, 2009 ) and electrical noise ( Wu et al, 2017 ). Moreover, previous research has suggested that the retina is susceptible to 8- to 20-Hz transcranial alternating current stimulation (tACS; Schutter and Hortensius, 2010 ; Kar and Krekelberg, 2012 ), which induces phosphenes even if the stimulation electrodes are placed over distal locations of the scalp ( Laakso and Hirata, 2013 ; for review, see Schutter, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…What remains unknown is whether tRNS-induced signal enhancement, and related contrast sensitivity benefits, could be achieved at the retinal level. Modelling studies suggest noise benefits in retinal ganglion cells ( Patel and Kosko, 2005 ) induced by both visual ( Ghosh et al, 2009 ) and electrical noise ( Wu et al, 2017 ). Moreover, previous research has suggested that the retina is susceptible to 8- to 20-Hz transcranial alternating current stimulation (tACS; Schutter and Hortensius, 2010 ; Kar and Krekelberg, 2012 ), which induces phosphenes even if the stimulation electrodes are placed over distal locations of the scalp ( Laakso and Hirata, 2013 ; for review, see Schutter, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…What remains unknown is whether tRNS-induced signal enhancement, and related contrast sensitivity benefits, could be achieved at the retinal level. Modelling studies suggest noise benefits in retinal ganglion cells (Patel and Kosko, 2005) induced by both visual (Ghosh et al, 2009) and electrical noise (Wu et al, 2017). Moreover, previous research has suggested that the retina is susceptible to 8-20Hz alternating currents (Kar and Krekelberg, 2012; Schutter and Hortensius, 2010) which induce phosphenes even if the stimulation electrodes are placed over distal locations of the scalp (Laakso and Hirata, 2013; see Schutter, 2016 for review).…”
Section: Introductionmentioning
confidence: 99%